1991
DOI: 10.1039/jm9910100271
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic ether–ketone–‘X’ polymers. Part 1.—Synthesis and properties

Abstract: A modified Friedel-Crafts synthesis has been used to make a variety of aromatic ether-ketone-')(' (EKX) polymers. The 'X' groups incorporated were: imide, amide, sulphone, ester, azo, quinoxaline, aliphatic, fluoroaliphatic and fluoroaromatic. Some properties of these EKX polymers are reported and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…The 13 C NMR spectrum of polymer 4ac in deuterio‐sulfuric acid (see the Experimental section) agreed quite well with that of the authentic poly(ether ketone), which was obtained separately by the polycondensation of diphenyl ether with 3c under similar Friedel–Crafts conditions mentioned previously, and further with that reported in the literature 20. There were five resonances in agreement with the expected para‐linked structure, and there was no evidence of the formation of ortho catenation.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The 13 C NMR spectrum of polymer 4ac in deuterio‐sulfuric acid (see the Experimental section) agreed quite well with that of the authentic poly(ether ketone), which was obtained separately by the polycondensation of diphenyl ether with 3c under similar Friedel–Crafts conditions mentioned previously, and further with that reported in the literature 20. There were five resonances in agreement with the expected para‐linked structure, and there was no evidence of the formation of ortho catenation.…”
Section: Resultssupporting
confidence: 86%
“…For the first time, we applied this fact to the polycondensation of bis(arylsilane)s with aromatic dicarboxylic acid chlorides under Friedel–Crafts acylation conditions and developed a new synthetic method for aromatic polyketones (Scheme ). Aromatic polyketones have usually been prepared by the aromatic electrophilic substitution polymerization of electron‐rich aromatic compounds such as diphenyl ether with aromatic dicarboxylic acid chlorides in the presence of Lewis acid catalysts 18–22. This article describes our new findings on the polycondensation of bis(arylsilane) monomers with aromatic dicarboxylic acid chlorides under Friedel–Crafts acylation conditions, which yielded ipso‐substituted aromatic polyketones.…”
Section: Introductionmentioning
confidence: 99%
“…It weighed 2.23 g (71%). The IR spectrum (NaCl) exhibited absorption bands at 3057 (aromatic COH), 2955 (CH 3 ), 1401 and 1111 (Si-aromatic), 1250 and 1165 (COOOC), and 1227 cm Ϫ1 (SiOCH 3…”
Section: Bis[3-(trimethylsilyl)phenyl] Ether (1a)mentioning
confidence: 99%
“…Aromatic polyketones are usually prepared by the aromatic electrophilic substitution polymerization of electron‐rich aromatic compounds such as diphenyl ether with aromatic dicarboxylic acid chlorides in the presence of Lewis acid catalysts under Friedel–Crafts acylation conditions 1–5. In a previous study,6 we demonstrated a new synthetic method of aromatic polyketones that involved the Friedel–Crafts‐type polycondensation of bis(arylsilane) monomers, in which the silyl groups were in the paraposition to the ortho/paradirecting groups, with aromatic dicarboxylic acid chlorides, along with the elimination of chlorotrimethylsilane.…”
Section: Introductionmentioning
confidence: 99%
“…Since k3 = 3 X 103 k 2 , at high substrate concentration, the overall rate of reaction reduces to k2wi]M, i.e. the forward reaction of eq 11 is the rate determining step. At low substrate concentration, the overall rate reduces to k3[MMt][Mt], i.e., eq 12 becomes the rate determining step.…”
Section: The C a --mentioning
confidence: 99%